Phylogenetic study on structural elements of HIV-1 poly(A) region. 1. PolyA and DSE hairpins - Zarudnaya, M.I.; Potyahaylo, A.L.; Kolomiets, I.M.; Hovorun, D.M. (Вiopolymers and Cell, 2013)
Genome of human immunodeficiency virus type 1 (HIV-1) is highly heterogeneous. The aim of this work was a phylogenetic study on structural elements of the HIV-1 poly(A) region, in particular polyA and DSE hairpins which compose a core poly(A) site. Methods. The secondary structure of the HIV-1 core poly(A) site has been predicted by the UNAFold program. Results. The structure of the polyA and DSE hairpins has been analysed in 1679 HIV-1 genomes of group M and 18 genomes of simian immunodeficiency virus SIVcpzPtt. We found 244 and 171 different sequences for the HIV-1 polyA and DSE hairpins, respectively. However 70 % of the HIV-1 isolates studied contain one of 7 variants of the polyA hairpin which occur with a frequency 5 % (main variants) and 79 % of the isolates contain one of 7 main variants of the DSE hairpin. We also revealed subtype and country specific mutations in these hairpins. We found that the SIV polyA hairpin most closely resembles that found in HIV-1 genomes of B/C subtypes. Conclusions. The results of our large-scale phylogenetic study support some structural models of the HIV-1 5' UTR, in particular the tertiary interaction between the polyA hairpin and the matrix region in HIV-1 gRNA. Possibly, the DSE hairpin appeared in the course of viral evolution of the HIV-1 group M. An exposure of the U/GU-rich element in the apical loop of DSE hairpin could significantly increase the efficiency of pre-mRNA polyadenylation in this HIV-1 group. Геном вірусу імунодефіциту людини (ВІЛ-1) надзвичайно гетерогенний. Мета. Провести філогенетичний аналіз структурних елементів області полі(А) ВІЛ-1, зокрема, шпильок поліA і DSE, які складають основний сайт полі(А). Методи. Передбачення вторинної структури основного полі(А)-сайта здійснювали за допомогою програми UNAFold. Результати. Структуру шпильок поліA і DSE проаналізовано для 1679 геномів ВІЛ-1 групи M та 18 геномів вірусу імунодефіциту мавп SIVcpzPtt: у геномах ВІЛ-1 виявлено 244 і 171 різна послідовність шпильок поліA і DSE відповідно. Однак 70 % вивчених геномів містили один із семи варіантів шпильки поліA, які зустрічалися з частотою 5 % (основні варіанти), і 79 % ізолятів вміщують один із семи основних варіантів шпильки DSE. Виявлено також специфічні для певного субтипу або країни мутації зазначених шпильок. Встановлено, що шпилька поліA з геному SIVcpzPtt дуже схожа на таку з геному ВІЛ-1 субтипів B і C. Висновки. Результати наших широкомасштабних досліджень підтримують деякі структурні моделі 5' нетрансльованої ділянки геному ВІЛ-1, зокрема, третинну взаємодію між шпилькою поліA і областю гена матриксного білка. Шпилька DSE, можливо, утворилася у процесі еволюції ВІЛ-1 групи М. Експонування U/GU-збагаченого елемента в апікальній петлі цієї шпильки могло значно підвищити ефективність поліаденілювання про-мРНК у ВІЛ-1 цієї групи. Геном ВИЧ-1 чрезвычайно гетерогенен. Цель. Провести филогенетический анализ структурных элементов области (поли)А ВИЧ-1, в частности, шпилек полиА и DSE, составляющих основной поли(А)-сайт. Методы. Вторичная структура основного поли(А)-сайта предсказана с помощью программы UNA Fold. Результаты. Структура шпилек полиА и DSE проанализирована в 1679 геномах ВИЧ-1 группы M и 18 геномах вируса иммунодефицита обезьян SIVcpzPtt: в геномах ВИЧ-1 выявлены соответственно 244 и 171 различная последовательность шпилек полиА и DSE. Однако 70 % изученных геномов содержат один из семи вариантов шпильки полиА, встречающихся с частотой 5 % (основные варианты) и 79 % изолятов содержат один из семи основных вариантов шпильки DSE. Обнаружены также варианты шпилек, специфические для определенного субтипа или страны. Выявлено, что шпилька полиА в геноме SIVcpzPtt наиболее близка по структуре таковой в геноме ВИЧ-1 субтипов В и С. Выводы. Результаты наших широкомасштабных исследований свидетельствуют в пользу некоторых структурных моделей 5' нетранслируемой области генома ВИЧ-1, в частности, наличия третичного взаимодействия между шпилькой полиА и участком в гене матриксного белка. Шпилька DSE, возможно, образовалась в процессе эволюции ВИЧ-1 группы М. Экспонирование U/GU- богатого элемента в апикальной петле шпильки DSE могло значи- тельно повысить эффективность полиаденилирования про- мРНК в ВИЧ-1 данной группы.